Bifunctional Initiators as Tools to Track Chain Transfer during the CROP of 2‐Oxazolines. Issue 19 (24th August 2017) - Sahn, Martin; Bandelli, Damiano; Dirauf, Michael; Weber, Christine; Schubert, Ulrich S.
Abstract : Four bifunctional, bromo‐type initiators are used and compared to benzyl bromide (BnBr) for the homopolymerization of 2‐ethyl‐2‐oxazoline (EtOx) to track chain transfer reactions during the polymerization process. Reaction solutions of the kinetic studies are investigated in detail by size exclusion chromatography (SEC) and matrix‐assisted laser desorption/ionization mass spectrometry (MALDI MS) to identify chain transfer products. Abstract : Detailed kinetic studies during the cationic ring‐opening polymerization (CROP) of 2‐ethyl‐2‐oxazoline (EtOx) are conducted using four bifunctional bromo‐type initiators in N, N ‐dimethylformamide (DMF) at 140 °C. Serving as models to quantify chain transfer to monomer occurring during the CROP initiated by monofunctional initiators, size exclusion chromatography (SEC) resolves a second molar mass distribution with lower molar mass at initial [monomer] to [initiation site] ratios ([M]0 /[I]0 ) of 25, while the resolution is insufficient at [M]0 /[I]0 of 10. Slightly slow initiation is revealed at [M]0 /[I]0 = 25, which prohibits the derivation of chain transfer rates by fitting of the size exclusion chromatography (SEC) data. Although conventional kinetic plots give no indication of significant amounts of chain transfer, the molar mass distributions resolved by SEC can unambiguously be identified as such by matrix‐assisted laser desorption/ionization mass spectrometry (MALDI MS) in both the high as well as the low m / z regions of the mass spectra.